Endogenous endothelin 1 mediates angiotensin II-induced hypertrophy in electrically paced cardiac myocytes through EGFR transactivation, reactive oxygenspecies and NHE-1 - Correa, María Verónica (2014)
Emerging evidence supports a key role for endothelin-1 (ET-1) and the transactivation of the epidermal growth factor receptor (EGFR) in angiotensin II (Ang II) action. We aim to determine the potential role played by endogenous ET-1, EGFR transactivation and redox-dependent sodium hydrogen exchanger-1 (NHE-1) activation in the hypertrophic response to Ang II of cardiac myocytes. Electrically paced adult cat cardiomyocytes were placed in culture and stimulated with 1 nmol l-1 Ang II or 5 nmol l-1 ET-1. Ang II increased ~45 % cell surface area (CSA) and ~37 % [3H]-phenylalanine incorporation, effects that were blocked not only by losartan (Los) but also by BQ123 (AT1 and ETA receptor antagonists, respectively). Moreover, Ang II significantly increased ET-1 messenger RNA (mRNA) expression. ET-1 similarly increased myocyte CSA and protein synthesis, actions prevented by the reactive oxygen species scavenger MPG or the NHE-1 inhibitor cariporide (carip). ET-1 increased the phosphorylation of the redox-sensitive ERK1/2-p90RSK kinases, main activators of the NHE-1. This effect was prevented by MPG and the antagonist of EGFR, AG1478. Ang II, ET-1 and EGF increased myocardial superoxide production (187 ± 9 %, 149 ± 8 % and 163.7 ± 6 % of control, respectively) and AG1478 inhibited these effects. Interestingly, Los inhibited only Ang II whilst BQ123 cancelled both Ang II and ET-1 actions, supporting the sequential and unidirectional activation of AT1, ETA and EGFR. Based on the present evidence, we propose that endogenous ET-1 mediates the hypertrophic response to Ang II by a mechanism that involves EGFR transactivation and redox-dependent activation of the ERK1/2-p90RSK and NHE-1 in adult cardiomyocytes.